Spatial organization of scincid lizards in Santubong Penin-sula, Sarawak, Borneo - Denzer, Wolfgang (Annals of Tropical Research, 1994)
This paper deals with the spatial organization within an assemblage of seven sympatric skinks from Borneo. The spatial segregation in different habitats as well as possible responses to potential competition of syntopic species is reported. Results from earlier reports are briefly discussed.